A Critical Appraisal of Concepts and Controversies - Abdullahi-Idiagbon, M. S. (Àgídìgbo: ABUAD Journal of the Humanities, 2013)
Discourse analysis has been defined in various ways but it seems the more the definitions increase, the more elusive and vague the concept becomes. The prevalent and preponderant meanings associated with discourse analysis emanating from its scope and interdisciplinary nature subsequently informing how the discipline is defined and conceptualised has consequently made imperative, the need to map out its terrain in order to narrow down the range of meaning and usage possibilities. The analyst should concentrate on those features that contribute to textual coherence. This paper has attempted to highlight the fundamentals of discourse analysis. shape its propensity and clear its controversies so that the discipline would be better appreciated.